2011
DOI: 10.1039/c0gc00509f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and ‘green’ microwave-assisted synthesis of haloalkylphosphonates via the Michaelis–Arbuzov reaction

Abstract: This paper deals with a novel, efficient and environmentally friendly synthesis of dialkyl haloalkylphosphonates via a microwave-assisted Michaelis-Arbuzov reaction. The approach is solventless, requires only one equivalent of each of the starting compounds, and provides high yields of pure products from which the impurities are easy to remove. The process has been optimised for batch and flow reactors and is especially profitable for the production of key intermediates in synthesis of Ethephon or acyclic nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
(15 reference statements)
1
26
0
Order By: Relevance
“…None of the 6-substituted FPMPA derivatives (13)(14)(15)(16)(17)(18)(19)(20)(21) showed neither anti-HIV nor anti-MSV activity in cell culture (Scheme 2). In contrast, several N 6 -substituted FPMPDAP derivatives were endowed with a moderate anti-HIV/MSV activity (Scheme 2, Table 2).…”
Section: Biological Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…None of the 6-substituted FPMPA derivatives (13)(14)(15)(16)(17)(18)(19)(20)(21) showed neither anti-HIV nor anti-MSV activity in cell culture (Scheme 2). In contrast, several N 6 -substituted FPMPDAP derivatives were endowed with a moderate anti-HIV/MSV activity (Scheme 2, Table 2).…”
Section: Biological Activitymentioning
confidence: 96%
“…Enantiomer 8a was also obtained in the same yield (67%) by an alternative procedure using bromomethylphosphonate 7 instead of tosylate 6 under similar reaction conditions. 20 Detritylation of compounds 8 was carried out in 80% aqueous acetic acid and gave acceptable yields of the derivatives 9. Scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 7-deazapurine compounds 10, 11 and 31, 32 were hydrolysed by the reaction with potassium carbonate and DABCO in water 30,31 to form 6-oxo-7-deazapurine derivatives 16, 17 and 37, 38. 32 was also tried. Thus, 6-chloropurine ester 9 was transformed directly to 6-oxopurine derivative containing free phosphonate functional groups, followed by conversion to the corresponding sodium salt of the final inhibitor 19 (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…According to the thermogravimetric analysis (TGA) of these biphosphonates and single phosphonates (DEEP Supported by the Jiangsu Natural Science Foundation of China (BK2011369) and Priority Academic Program Development of Jiangsu Higher Education Institutions and DMMP), results showed that biphosphonates had better thermal stability and higher char residue, two important measures of low flammability materials. These flame retardants were synthesized through polycondensation and Arbuzov rearrangement reactions [11] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%